Insights into the bioluminescence systems of three sea pens (Cnidaria: Anthozoa): from de novo transcriptome analyses to biochemical assays - Laurent Duchatelet; Gabriela A. Galeazzo; Constance Coubris; Laure Bridoux; René Rezsohazy; Marcelo R. S. Melo; Martin Marek; Danilo T. Amaral; Sam Dupont; Anderson Garbuglio de Oliveira; Jérôme Delroisse (Open Biology)
Bioluminescence is the production of visible light by living organisms. It occurs through the oxidation of luciferin substrates catalysed by luciferase enzymes. Auxiliary proteins, such as fluorescent proteins and luciferin-binding proteins, can modify the light emitted wavelength or stabilize reactive luciferin molecules, respectively. Additionally, calcium ions are crucial for the luminescence across various species. Despite the large phylogenetic distribution of bioluminescent organisms, only a few systems have been comprehensively studied. Notably, cnidarian species of the Renilla genus utilize a coelenterazine-dependent luciferase, a calcium-dependent coelenterazine-binding protein and a green fluorescent protein. We investigated the bioluminescence of three sea pen species: Pennatula phosphorea, Anthoptilum murrayi and Funiculina quadrangularis (Pennatuloidea, Anthozoa). Their light-emission spectra reveal peaks at 510, 513 and 485 nm, respectively. A coelenterazine-based reaction was demonstrated in all three species. Using transcriptome analyses, we identified transcripts coding for luciferases, green fluorescent proteins and coelenterazine-binding proteins for P. phosphorea and A. murrayi. Immunodetection confirmed the expression of luciferase in P. phosphorea and F. quadrangularis. We also expressed recombinant luciferase of A. murrayi, confirming its activity. We highlighted the role of calcium ions in bioluminescence, possibly associated with the mechanism of substrate release at the level of coelenterazine-binding proteins. The study proposes a model for anthozoan bioluminescence, offering new avenues for future ecological and functional research on these luminous organisms.